Pattern of Otorhinolaryngological Diseases at Rural Medical Camps in Far Western Region of Nepal - Karki, Reeba; Rai, Kiran (Medical Journal of Shree Birendra Hospital, 2013)
Introduction: Nepal army has been organizing free medical camp in various parts of Nepal since many years. The free medical camp is committed to improve global health care in rural parts of Nepal. This study was conducted to describe the demographic and ENT-HNS diseases among the patients attending medical camps in two rural parts of far western region of Nepal (Humla-Simikot and Muggu- Talcha) Methods: Retrospective studies of all the patients attending ENT-HNS clinic of Simikot and Talcha medical camp from October 12th to October 16th 2011 were evaluated. Each patient was assessed by consultant ENT-Head and Neck surgeon. Only adult age group patient were included in the study. The disease was divided into four group i.e otology (ear disease), rhinology (nose disease), head and neck (throat disease) and normal finding groups. Results: Total numbers of 213 patients were analyzed in Simikot and 167 patients in Talcha. Among them otology group were 80 patients (37.5%), rhinology 57patients (26.7%), head and neck 55patients (25.82%) and 21 patients (9.85%) had normal findings in Simikot. Similarly in Talcha the patients were 84(50.29%) in otology, 22(13.17%) in rhinology, 49(29.34%) in head and neck and12 (7.1%) with normal findings respectively. Conclusions: Chronic otitis media (CSOM) is the most common ENT problems in both the rural areas. One of the major causes of hearing loss is CSOM so improvement of socioeconomic status and health care facilities will also be helpful in reducing the prevalence of CSOM. Medical Journal of Shree Birendra Hospital; July-December 2012/vol.11/Issue2/29-31 DOI: http://dx.doi.org/10.3126/mjsbh.v11i2.7906